2020
DOI: 10.1111/1440-1681.13338
|View full text |Cite
|
Sign up to set email alerts
|

The anti‐tumourigenic effect of ellagic acid in SKOV‐3 ovarian cancer cells entails activation of autophagy mediated by inhibiting Akt and activating AMPK

Abstract: This study investigated the effect of ellagic acid (EA) on SKOV‐3 cell growth and invasiveness and tested if the underlying mechanism involves modulating autophagy. Cells were treated with EA in the presence or absence of chloroquine (CQ), an autophagy inhibitor, compound C (CC), an AMPK inhibitor, or an insulin‐like growth factor‐1 (IGF‐1), a PI3K/Akt activator. EA, at an IC50 of 36.6 µmol/L, inhibited cell proliferation, migration, and invasion and induced cell apoptosis in SKOV‐3 cells. These events were pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Duan et al reported that ellagic acid (10-50 µM) activated autophagy, but not apoptosis, in lung cancer cells (HOP62 and H1975), and in tumor-bearing mice (40 mg/kg, i.p., every 2 days, for 22 days), as demonstrated by the formation of LC3-positive autophagosomes, the increase in LC3 II, ATG5 and the reduced levels of p62 [238]. Similarly, ellagic acid (36.6 µM) inhibited cell growth and the invasiveness of ovarian cancer SKOV-3 cells and stimulated apoptosis by activating cytotoxic autophagy, as indicated by the increase in the levels of Beclin 1, ATG5, LC3I/II and decrease in p62 [239]. In addition, it was shown that ellagic acid activated autophagy through the downregulation of mTORC1 and Akt, and the activation of AMPK [238,239].…”
Section: Phenolic Acidsmentioning
confidence: 97%
See 1 more Smart Citation
“…Duan et al reported that ellagic acid (10-50 µM) activated autophagy, but not apoptosis, in lung cancer cells (HOP62 and H1975), and in tumor-bearing mice (40 mg/kg, i.p., every 2 days, for 22 days), as demonstrated by the formation of LC3-positive autophagosomes, the increase in LC3 II, ATG5 and the reduced levels of p62 [238]. Similarly, ellagic acid (36.6 µM) inhibited cell growth and the invasiveness of ovarian cancer SKOV-3 cells and stimulated apoptosis by activating cytotoxic autophagy, as indicated by the increase in the levels of Beclin 1, ATG5, LC3I/II and decrease in p62 [239]. In addition, it was shown that ellagic acid activated autophagy through the downregulation of mTORC1 and Akt, and the activation of AMPK [238,239].…”
Section: Phenolic Acidsmentioning
confidence: 97%
“…Similarly, ellagic acid (36.6 µM) inhibited cell growth and the invasiveness of ovarian cancer SKOV-3 cells and stimulated apoptosis by activating cytotoxic autophagy, as indicated by the increase in the levels of Beclin 1, ATG5, LC3I/II and decrease in p62 [239]. In addition, it was shown that ellagic acid activated autophagy through the downregulation of mTORC1 and Akt, and the activation of AMPK [238,239]. The activation of apoptotic and autophagic cell death was also reported for punicalagin, an ellagitannin isolated from the fruit of Punica granatum L. trees.…”
Section: Phenolic Acidsmentioning
confidence: 99%
“…The antitumorigenic potential of ellagic acid confirmed in SKOV-3 OC cells involved cytotoxic autophagy activation mediated by Akt inhibition and AMPK activation. Mechanistically, it decreased the levels of the two downstream targets, mTORC1 and p-Akt, but increased the levels of AMPK (Thr172) [ 78 ]. PI3K/Akt inhibits autophagy by activating mTORC1, and AMPK inhibits mTORC1, thus activating autophagy.…”
Section: Phenolic Acids Involved In the Regulation Of Molecular Targetsmentioning
confidence: 99%
“…EA also inhibits angiogenesis by inhibiting growth factor VEGF secretion [ 43 ]. Ellagic acid-induced apoptotic induction (caspase-3 mediated via an increased Bax: Bcl-2 ratio and JNK and Akt phosphorylation) and cytotoxic autophagy activation (Akt inhibition and AMPK activation) enhances the efficacy of EA-based chemotherapy [ 74 , 78 ]. Thus, the key role in cellular apoptosis and dysregulated autophagy in ovarian cancer development and progression indicates its potential as a promising therapeutic target.…”
Section: Summary and Future Perspectivesmentioning
confidence: 99%
“…The p21 and p53 levels undergo upregulation by ellagic acid to induce apoptosis in prostate cancer cells [ 207 ]. The ellagic acid stimulates autophagy via Akt down-regulation and AMPK upregulation to reduce viability and survival of ovarian cancer cells [ 208 ]. The ellagic acid is a potent agent in suppressing drug resistance via down-regulating P-glycoprotein (P-gp_levels [ 209 ].…”
Section: Dietary Agents and Cancer Stem Cellsmentioning
confidence: 99%